A systematic review of studies validating the Edinburgh Postnatal Depression Scale in antepartum and postpartum women. - Gibson, J; McKenzie-McHarg, K; Shakespeare, J; Price, J; Gray, R (2009)
OBJECTIVE: The Edinburgh Postnatal Depression Scale (EPDS) is the most widely used screening tool for postpartum depression (PPD). We systematically reviewed the published evidence on its validity in detecting PPD and antepartum depression (APD) up to July 2008. METHOD: Systematic review of validation studies of the EPDS included 1987-2008. Cut-off points of 9/10 for possible PPD, 12/13 for probable PPD and 14/15 for APD were used. RESULTS: Thirty-seven studies met the inclusion criteria. Sensitivity and specificity of cut-off points showed marked heterogeneity between different studies. Sensitivity results ranged from 34 to 100% and specificity from 44 to 100%. Positive likelihood ratios ranged from 1.61 to 78. CONCLUSION: Heterogeneity among study findings may be due to differences in study methodology, language and diagnostic interview/criteria used. Therefore, the results of different studies may not be directly comparable and the EPDS may not be an equally valid screening tool across all settings and contexts.